Karakterisasi Protein Hemaglutinin Subunit Pili Pasteurella multocida serotipe B:2 = Characterization Of .Hemagglutinin Protein Pili Subunit Pasteurella multocida serotype B:2 - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT The character of hemagglutinin of pili subunit Pasteurella multocida serotype B:2 causing haemorragic septicaemia (HS) in cattle and buffalo had not been known yet. The purpose of this experiment was to isolate and characterize hemagglutinin subunit pili of Pasteurella multocida B:2, and to determine its role on atachment process to the epithelium of trachea. The experiment was devided into some steps including cultivation of P. multocida B:2 Kupang isolate using bifasic medium, and pili isolation using Ehara (1986) methode. Then isolation and characterisation of hemagglutinin protein was performed consisting of protein pili subunit separation using 12% SDS-PAGE, electroelution, hemagglutination test according to Hanne and Finkeltein methode. Production of policlonal antibody againts hemagglutinin protein was conducted in 24 week old Lohman chicken, with 3 times subcutaneous imunisation. Isolation of antibody from egg was conducted using PEG 6000 based on Gassmann et al. (1990) methode. The antibody specifity was tested using immunoblotting. The role of hemagglutinin was investigated by hemagglutinin inhibition test employing Freter and Jones methode and attachment inhibition test of bacteria to epithelium trachea. The result showed that there were two type of hemagglutinin protein with molecular weight of 32 kDa and 66 kDa. The antibody against hemagglutinin 32 kDa reacted to 32 and 28 kDa protein pili subunit, while antibody againts hemagglutinin 66 kDa could only react to 66 kDa hemagglutinin protein. Hemagglutinin protein was suspected to take part in atachment process of bacteria to epithelium trachea.